2021
DOI: 10.1186/s40795-021-00482-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry/red grape juice decreases plasma biomarkers of inflammation and tissue damage in aged men with subjective memory impairment –a randomized clinical trial

Abstract: Background Few randomized clinical trials have explored the health effects of bilberries in humans. The aim was to test the effect of bilberry and red grape-juice consumption on visual memory, motor speed and dexterity as well as inflammatory and tissue damage biomarkers of plasma in aged men with subjective memory impairment. Methods Nine-week double-blind, placebo-controlled, dietary intervention study of aged men (n = 60, age ≥ 67 years) with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Dihydrocaffeic acid is a compound that is observed in samples of plasma, urine, or faeces after the consumption of products with a high content of chlorogenic and caffeic acids, which indicates, e.g., the activity of intestinal microbiota on the metabolic fate of these compounds. In recent years, scientists have examined what happens to the phenolic compounds that are ingested along with the following food products: coffee, yerba mate, cocoa, and artichoke, as well as berry, grape, and apple products [40][41][42][43][44][45][46][47][48][49][50].…”
Section: Metabolism Of Dihydrocaffeic Acid By Intestinal and Lactic A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dihydrocaffeic acid is a compound that is observed in samples of plasma, urine, or faeces after the consumption of products with a high content of chlorogenic and caffeic acids, which indicates, e.g., the activity of intestinal microbiota on the metabolic fate of these compounds. In recent years, scientists have examined what happens to the phenolic compounds that are ingested along with the following food products: coffee, yerba mate, cocoa, and artichoke, as well as berry, grape, and apple products [40][41][42][43][44][45][46][47][48][49][50].…”
Section: Metabolism Of Dihydrocaffeic Acid By Intestinal and Lactic A...mentioning
confidence: 99%
“…Dihydrocaffeic acid derivatives evaluated as anticancer agents. Chemical structures of: isopropyl dihydrocaffeate ( 45), tert-butyl dihydrocaffeate (46), benzyl dihydrocaffeate (47), 3-phenylpropyl dihydrocaffeate (48). 3.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with isotopically labeled molecules have also confirmed these observations. Albeit hippuric acids are widely recognized as biomarkers of (poly)phenol consumption (Bøhn et al., 2021; Yuan et al., 2022), they are also produced from endogenous pathways, that is, phenylalanine metabolic pathway (Zhang et al., 2021). This may lead to their continuous production in humans and the fact that it is present in longer timepoints.…”
Section: Lmw Phenolic Metabolites: Blood Distribution and Pharmacokin...mentioning
confidence: 99%
“…As free radical stress and inflammation are closely related, an inflammatory response increases ROS production, maintaining a pro-inflammatory environment. In one study, bilberry/red grape juice consumption (660 mL per day) improved oxidative stress and inflammation biomarkers in a double-blind, placebo-controlled, intervention study ( n = 60) [ 81 ]. The intervention decreased the levels of biomarkers of inflammation (epidermal growth factor [EGF], IL-6, TNF-α, macrophage inflammatory protein [Mip]1β, and vascular endothelial growth factor [VEGF]) and tissue damage (lactate dehydrogenase [LDH]); however, the memory score was unaffected.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%